Simultaneous quantification of seventeen bioactive components in rhizome and aerial parts of Alpinia officinarum Hance using LC-MS/MS. Issue 12 (21st June 2015) - Zhang, Jun-Qing; Wang, Yong; Li, Hai-Long; Wen, Qi; Yin, Hang; Zeng, Nian-Kai; Lai, Wei-Yong; Wei, Na; Cheng, Shou-Qian; Kang, Sheng-Li; Chen, Feng; Li, You-Bin
<x xml:space="preserve">Abstract</x> Simultaneous quantification of 17 phytochemicals in rhizome and aerial parts of Alpinia officinarum Hance sampled at different growing periods using LC-MS/MS.